Combinatorics on words 9th International Conference, WORDS 2013, Turku, Finland, September 16-20. Proceedings - Lepisto, Arto; Zamboni, Luca; Karhumaki, Juhani (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 9th International Conference on Combinatorics on Words, WORDS 2013, held in Turku, Finland, in September 2013 under the auspices of the EATCS. The 20 revised full papers presented were carefully reviewed and selected from 43 initial submissions. The central topic of the conference is combinatorics on words (i.e. the study of finite and infinite sequence of symbols) from varying points of view, including their combinatorial, algebraic and algorithmic aspects, as well as their applications.